Strategi Green Construction dalam Konstruksi Berkelanjutan Untuk Bangunan Gedung Ramah Lingkungan Dan Ekonomis di Indonesia - Mahardika, Daffa; Dewanti, Rizci Purna; Subagyo, Arief (Metta : Jurnal Ilmu Multidisiplin, 2025)
Infrastructure development in Indonesia continues to grow, yet the construction sector still negatively impacts the environment, including high resource consumption and excessive waste production. Green Construction emerges as a sustainable solution by implementing energy efficiency, environmentally friendly materials, and improved waste management. This study aims to analyze the effectiveness of Green Construction in Indonesia by evaluating its implementation in building projects using a qualitative research approach with literature review and case study analysis. The methodology includes an extensive review of existing research, policy documents, and case studies of Green Building-certified projects. The analysis focuses on key principles such as energy efficiency, water conservation, sustainable material selection, and the role of digital technology, particularly Building Information Modeling (BIM). Data were collected from various academic and government sources to provide a comprehensive understanding of Green Construction practices. The results indicate that Green Construction adoption has increased, with a rising number of projects implementing sustainable building strategies. Energy-efficient systems, eco-friendly materials, and improved waste management practices have been successfully integrated into several high-profile construction projects. However, significant challenges remain, including regulatory limitations, high initial investment costs, and low awareness among industry players. Case studies demonstrate that Green Construction can reduce energy consumption by up to 30% and operational costs by 20%, proving its economic viability. Despite these obstacles, Green Construction offers substantial environmental, economic, and social benefits. It reduces carbon emissions, promotes resource conservation, and enhances indoor air quality, leading to healthier living environments. Strengthening government policies, providing financial incentives, and increasing investment in sustainable technology are crucial for accelerating Green Construction implementation in Indonesia. With comprehensive strategies and collaborative efforts, Green Construction can significantly contribute to achieving Indonesia’s sustainable development goals by fostering a more eco-friendly and efficient construction sector.